(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This study evaluates the impact of retrograde condensation on gas deliverability in gas-condensate reservoirs experiencing pressure decline below the dewpoint, and examines methods for mitigating the associated productivity losses. As reservoir pressure drops below the dewpoint pressure during depletion, heavy hydrocarbon components condense from the gas phase, forming a liquid condensate ring around the wellbore that reduces the effective gas permeability and severely impairs well productivity. Employing a compositional reservoir simulation approach calibrated with laboratory PVT data from three gas-condensate fields in Central Asia, this study quantifies the magnitude of deliverability loss under varying reservoir and fluid conditions. Simulation results demonstrated that retrograde condensation reduced gas deliverability by 35–68% depending on fluid richness and distance of pressure decline below the dewpoint. Comparative analysis of four mitigation strategies pressure maintenance through lean gas cycling, hydraulic fracturing, chemical wettability alteration, and periodic well blowdown revealed that gas cycling maintained the highest sustained deliverability (87–93% of original capacity), while chemical treatment provided the most cost-effective short-term improvement for mature fields. These findings provide a quantitative framework for reservoir management decision-making and carry implications for the optimization of gas-condensate field development strategies in the region.